2020
DOI: 10.1016/j.jcot.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Gustilo-Anderson type III tibial fractures have poor functional outcomes in patients over 75 years

Abstract: Background: Previous outcome studies in open tibial fractures have commonly assessed young patients and there is a paucity of data regarding outcomes in the elderly. The aim of this study is to assess functional outcomes for patients over 75 years with Gustilo-Anderson Grade III open tibial fractures, including mobility and residential status. Methods: Outcomes for all patients over 75 years admitted with grade III open tibial fractures to a UK level 1 trauma centre during a 5-year period (January 2010eMay 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The bimodal age and gender distribution of open tibia/fibula fractures in this study are consistent with previous UK data. 21 , 22 , 23 This study demonstrated a similar soft tissue insult in terms of Gustilo-Anderson classification despite the difference in mechanism. This observation may be explained by skin fragility and systemic frailty, 22 , 24 allowing a greater degree of tissue destruction despite lower forces involved.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The bimodal age and gender distribution of open tibia/fibula fractures in this study are consistent with previous UK data. 21 , 22 , 23 This study demonstrated a similar soft tissue insult in terms of Gustilo-Anderson classification despite the difference in mechanism. This observation may be explained by skin fragility and systemic frailty, 22 , 24 allowing a greater degree of tissue destruction despite lower forces involved.…”
Section: Discussionsupporting
confidence: 60%
“… 36 Compared to previous data we report lower rates of amputation overall; this may relate to the lower proportion of Gustilo-Anderson grade 3 injuries in our cohort. 23 , 26 Additionally, despite similar operative interventions across both age groups, elderly patients had a significantly longer time to discharge. Length of stay in both age groups was comparable with previous reports.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The host status, already has classification tools available 31 . Perhaps elderly patients need to be considered differently as it has been shown outcomes are worse in this cohort 32 . However, the risk of doing so is to potentially undermine the whole concept of developing a very simplistic grading system.…”
Section: Discussionmentioning
confidence: 97%